Experience of the use of electronic training in the educational process of the Russian higher educational institution - V. Kamenez, Natalia; Igorevna Vaganova, Olga; Venediktovna Smirnova, Zhanna; Nikolaevan Bulayeva, Marina; Andreevna Kuznetsova, Ekaterina; Maseleno, Andino (International Journal of Engineering and Technology, 2018)
To date, the problem of intensifying the learning process is one of the most pressing problems in vocational education in Russia. The article reveals the elements that influence the development of open electronic courses by universities. The advantages of e-courses are named. The opinions on the main opportunities and limitations in the conditions arising in the process of e-learning are analyzed. Ways of intensification should be allocated with the view of use in the educational process of modern digital technologies. In connection with the development of educational technologies in combination with the use of digital resources and their intensive updating, their impact on the quality of education should be constantly studied. The purpose of the article is to analyze the experience of using e-learning in the educational process of the Russian higher educational institution. In the Minin Nizhny Novgorod State Pedagogical University as well as in the Industrial University of Tyumen a survey was conducted on the satisfaction with the use of e-learning by students and teachers. 94 teachers and 214 students participated in the study. To conduct the study, a questionnaire was created consisting of three blocks of questions: "The relevance of e-learning in the learning process", "The level of use of e-learning and its elements in the learning process" and "Self-assessment of teacher’s competencies in e-learning technologies". The results of the research showed high satisfaction of students and teachers with e learning.